Baicalein Mitigates Radiation-Induced Enteritis by Improving Endothelial Dysfunction - Jang, Hyosun; Lee, Janet; Park, Sunhoo; Kim, Joong Sun; Shim, Sehwan; Lee, Seung Bum; Han, Sung-Honn; Myung, Hyunwook; Kim, Hyewon; Jang, Won-Suk; Lee, Sun-Joo; Myung, Jae kyung (Frontiers in Pharmacology, 2019)
Background and Aims: Radiation-induced intestinal injury occurred in application of radiotherapy for abdominal and pelvic cancers or in nuclear accidents. Radiation-induced enteritis may be considered an ideal model of gastrointestinal inflammation. The endothelium is a crucial component of inflammation, and the endothelial dysfunction following radiation exposure induces the intestinal proinflammatory response and progression of radiation enteritis. Baicalein (5,6,7-trihydroxyflavonoid) is a flavonoid from Scutellaria baicalensis used in oriental herbal medicine. Baicalein has been found to have multiple beneficial properties including antioxidant, anti-inflammatory, anti-allergic, and anti-cancer activities. Here, we investigated the therapeutic effects of baicalein on endothelial dysfunction in radiation-induced intestinal inflammation. Materials and Methods: We performed histological analysis, bacterial translocation, and intestinal permeability assays and also assessed infiltration of leukocytes and inflammatory cytokine expression using a mouse model of radiation-induced enteritis. In addition, to investigate the effect of baicalein in endothelial dysfunction, we analyzed endothelial-derived adherent molecules in human umbilical vein endothelial cells (HUVECs) and irradiated intestinal tissue. Results: Histological damage such as shortening of villi length and impaired intestinal crypt function was observed in the radiation-induced enteritis mouse model. Intestinal damage was attenuated in baicalein-treated groups with improvement of intestinal barrier function. Baicalein inhibited the expression of radiation-induced adherent molecules in HUVECs and intestine of irradiated mouse and decreased leukocyte infiltration in the radiation-induced enteritis. Conclusions: Baicalein could accelerate crypt regeneration via recovery of endothelial damage. Therefore, baicalein has a therapeutic effect on radiation-induced intestinal inflammation by attenuating endothelial damage.